Margarin från Hangö - Malmén, Yngve (Tekniikan Waiheita, 2008)
Margarine from Hangö A hundred years ago, the port city of Hangö (Finn. Hanko) was well known for its production and exportation of butter. For example, the headquarters of Valio dairy company was located in Hangö from 1905 till the First World War. Hangö has also played an important role in the early production of margarine in Finland. The article sheds light on the political resistance that was encountered by the first Hangö-based companies with their plans to start margarine production. The article analyzes also production processes, the end products and their ingredients, and how they were advertised. During the Second World War the city of Hangö had to be evacuated, which was fatal to the city’s margarine industry.